Winegrapes dehydration under ozone-enriched atmosphere: Influence on berry skin phenols release, cell wall composition and mechanical properties. (15th January 2019) - Río Segade, Susana; Paissoni, Maria Alessandra; Giacosa, Simone; Bautista-Ortín, Ana Belén; Gómez-Plaza, Encarna; Gerbi, Vincenzo; Rolle, Luca
Highlights: Impact of gaseous ozone during dehydration of two winegrape varieties was studied. Ozone effects strongly depended on the profile and content of phenolic compounds. Anthocyanin extraction was higher in treated Barbera but lower in Nebbiolo. Oligomeric and polymeric flavanol extraction was poorly affected by ozone treatment. Phenolic extraction, cell wall composition and texture traits were strongly related. Abstract: Gaseous ozone has been recently proposed as sanitizing agent to control mycobiota on grapes. The aim of this work was to evaluate the impact of ozone treatment during winegrapes dehydration (10 and 20% weight loss) on the content of phenolic compounds after treatment and their extractability during simulated maceration. The results showed that the ozone effect depends on the profile and content of anthocyanins and flavanols. For varieties characterized by prevalence of di-substituted anthocyanins and high flavanol contents, no significant differences were observed in phenolic compounds contents, but lower anthocyanin extractability was found. Instead, for varieties rich in anthocyanins and with a tri-substituted prevalent profile, lower anthocyanin contents were found at 20% WL, but their extractability was significantly increased. Using multivariate analysis, the extractability was correlated with skin cell wall composition and mechanical properties. Proteins, non-cellulosic glucose and total phenols contributed mainly to explain phenolic compounds extractability in withered grapes.